Polymerizable organo-gelator-stabilized gel-emulsions toward the preparation of compressible porous polymeric monoliths. Issue 39 (20th September 2016) - Fu, Xuwei; Wang, Pei; Miao, Qing; Liu, Kaiqiang; Liu, Huijing; Liu, Jianfei; Fang, Yu
Abstract : Compressible porous polymeric monoliths could be used as highly efficient formaldehyde and toluene adsorbents. Abstract : Compressible porous monoliths are important for isolation and separation processes. However, preparation via a gel-emulsion method suffers from high cost, partially due to the consumption of too much stabilizer and less tunability in both mechanical properties and internal structures. To cope with the challenges, a polymerizable cholesteryl derivative (CEA) was designed and used as a stabilizer of gel-emulsions. In addition, a derivative of poly(oligo)-dimethylsiloxane with two olefinic bonds at its ends (D-PDMS) was also purposely prepared and employed as a cross-linker for the system. In this way, gel-emulsions with a mixture of toluene, n -heptane, CEA, and D-PDMS as the continuous phase and water as the dispersed phase were prepared. As expected, polymerization of the continuous phase resulted in porous polymeric monoliths. Interestingly, the internal structures of the materials could be largely adjusted via simple variation of the ratio of n -heptane to toluene in the continuous phase. Moreover, utilization of the specially synthesized cross-linker endows the monoliths with flexibility, which must bring convenience for real-life applications. Adsorption tests demonstrated that the porous materials were good adsorbents of formaldehyde (∼1300 mg g −1 ) and toluene (∼900 mg g −1 ) at ambient conditions, and they were reusable after simple washing and drying. Considering the simplest material in the preparation including ambient pressure drying without solvent exchange, the superior performance in the adsorption tests and the fact that the as-created CEA could function both as a monomer and a stabilizer, it is believed that the work presented here represents substantial progress of the techniques used for the preparation of porous polymeric materials. Moreover, the monolith demonstrates new records for the adsorption of toxic formaldehyde and toluene from contaminated air.